Prevalence of Phenylthiocarbamide (PTC) Taste Sensitivity at The Population of Gili Ketapang Island in Probolinggo Regency - Oktarianti, Rike; Wulandari, Siti Agustina; Wiyono, Hidayat Teguh; Mahriani, Mahriani (Metamorfosa: Journal of Biological Sciences, 2023)
The taste of sensitivity of   Phenylthiocarbamide (PTC), is autosomal dominant trait inherited. The taster controled by dominant allele while the   non-taster determinated by recessive allele. The purpose of this study was to determine the prevalence and frequency of taster and non-taster alleles for PTC, as well as non-taster inheritance patterns at the population of Gili Ketapang island, Probolinggo district. Determination of the sample or respondents was carried out by randomly, total sample were 384 people, aged from 15-30 years. Detection of the taste sensitivity PTC was ask to respondents to taste the PTC solution. The PTC solution used was from the lowest concentration of 0.32mg/L (P13) to the highest concentration of 1300 mg/L (P1). The results showed that the prevalence of taster and non-taster were 96.88% and 3.12%, respectively. The frequency of taster (T) and non-taster alleles was 0.83 and non-taster was 0.17. The  pedigree analysis of non-taster showed that non-tast er individuals were born from heterozygous taster pairs (Tt) or from marriages between heterozygous taster individual (Tt) with non-tasters (tt). Keyword : Phenylthiocarbamide (PTC), taster, non taster